Urinary 8-OxoGsn as a Potential Indicator of Mild Cognitive Impairment in Frail Patients With Cardiovascular Disease - Yao, Si-Min; Zheng, Pei-Pei; He, Wei; Cai, Jian-Ping; Wang, Hua; Yang, Jie-Fu (Frontiers in aging neuroscience, 2021)
Oxidative RNA damage has been found to be associated with age-related diseases and 8-oxo-7,8-dihydroguanosine (8-oxoGsn) is a typical marker of oxidative modification of RNA. Urine tests are a feasible non-invasive diagnostic modality. The present study aimed to assess whether the measurement of urinary 8-oxoGsn could represent a potential early maker in mild cognitive impairment (MCI) of frail patients with cardiovascular disease (CVD). In this cross-sectional study performed in China from September 2018 to February 2019. Urinary 8-oxoGsn was measured in frail (Fried phenotype: 3–5) in patients with CVD and was adjusted by urinary creatinine (Cre) levels. Cognitive function was assessed by the Chinese version of the Mini-Mental State Examination (MMSE) and participants were classified into non-MCI (≥24) and MCI (<24) groups. Univariate and multivariate logistic regression models were used to determine the relationship between 8-oxoGsn/Cre and MCI. Receiver operating characteristic (ROC) curve analysis was used to assess the 8-oxoGsn/Cre ratio in relation to MCI in frail patients with CVD. A total of 106 elderly patients were enrolled in this study. The mean age of participants was 77.9 ± 6.8 years, the overall prevalence of MCI was 22.6% (24/106), and 57.5% (61/106) of participants were women. In the multivariate logistic regression analysis, urinary 8-oxoGsn/Cre was independently associated with MCI (odds ratio [OR] = 1.769, 95% confidence interval [CI] = 1.234–2.536, P = 0.002), after adjusting for age, sex, education level, marital status, and serum prealbumin levels. The area under the ROC curve was 0.786 (0.679–0.893) ( P < 0.001), and the optimal cut-off value was 4.22 μmol/mol. The urinary 8-oxoGsn/Cre ratio showed a sensitivity of 87.5% and a specificity of 69.5%. The present study suggests the urinary 8-oxoGsn/Cre ratio may be a useful indicator for the early screening of MCI in frail patients with CVD.